SISTEM PENGONTROLAN KADAR GARAM AIR PADA AKUARIUM IKAN HIAS AIR LAUT MENGGUNAKAN METODE FUZZY LOGIC MAMDANI - n/a Rifyal; Tri Nurwati; Eka Maulana (Jurnal Mahasiswa TEUB, 2022)
Ornamental fish is one of the major export commodities, besides that, there are also many domestic marine ornamental fish hobbyists. The maintenance of seawater ornamental fish needs to pay attention to the level of salt or salinity so that the fish can survive. Manually adjusting the salt level of seawater is not efficient and must be checked continuously. Therefore, an automatic salt level controller is needed. In this study, the sensor design process was carried out using the YL-69 sensor and pump speed regulation. From the results of this study, it can be seen that the tool can balance the salt content according to the setpoint membership function fuzzy, which is 32-37 ppt for 564-768 seconds. The water discharge coming out of the pump can also be adjusted according to the difference in the salt content of the aquarium with the desired value.Keywords: Salinity, fuzzy, membership function.